A study to assess the knowledge and attitude towards HIV/AIDS among adolescents studying in higher secondary school in Inaruwa, Sunsari District, Nepal - Prasad Mehta, Yogendra (Indian Journal of Nursing Sciences, 2024)
The human immunodeficiency virus (HIV) is a retrovirus that infects cells of the human immune system, destroying or impairing their function. HIV/AIDS (Acquired Immune Deficiency Syndrome) is a present public health problem, viewed more optimistically as a communicable disease. Aim: To examine the knowledge and attitude toward HIV/AIDS among adolescent studying in higher secondary school. Method: A descriptive cross-sectional research design was used to identify the present knowledge and attitude of adolescents studying at higher secondary school Inaruwa, Sunsari district towards HIV/AIDS. A total number of 180 students were selected by probability sampling technique from two school, Nawayug Higher School and Sharada Higher Secondary school. A self administered structured questionnaire was developed to assess the knowledge and attitude toward HIV/AIDS people. Inferential statistics (Chi- square test) was used to examine the relationship between the knowledge and attitude toward HIV/AIDS, relationship between adolescents' background characteristics and knowledge and attitude toward HIV/AIDS, and relationship between selected background characteristics and knowledge about mode of transmission of HIV/AIDS, prevention , prevention of HIV from mother to child and sources that HIV not transmitted. Result: This study showed that total knowledge level of 56.2 percent of respondents have average, of 22.5 percent have excellent and 21.3 percent have poor whereas, total attitude level of 52.2 percent have favorable attitude towards HIV/AIDS peop